A review of supercritical CO2 Brayton cycle using in renewable energy applications - Wenxiao Chu; Katrine Bennett; Jie Cheng; Yi-Tung Chen (Renewable Energy and Sustainable Development, 2018)
The carbon dioxide (CO2), which is an environmental friendly working fluid, has good thermal physical properties under the supercritical condition. The heat transfer mechanism and the enhanced heat transfer method of the supercritical CO2 Brayton cycle (SCO2-BC) have been studied by many researchers, which can be used in the new generation of Fast Cooling Reactor (FCR), solar power system, extraction progress and heat pump system. With the development of engineering technology, the system miniaturization is the most important characteristics in application, which the SCO2-BC can satisfy the requirements with high efficiency and high compactness. In the present paper, the research progress of SCO2-BC including the performance evaluation, system optimization and economic evaluation are reviewed based on the references in recent years. Then, the analysis of the key components including the compressor, turbine and heat exchanger are introduced with the special thermal properties of supercritical CO2, which are different from the conventional devices in the traditional steam cycle. Finally, some recommendations for future work are primarily proposed towards the development of SCO2-BC system.